Artificial removal of the zona pellucida at the pronuclear stage: an exploratory study to improve embryo fragmentation - Keitaro Yumoto, B.Sc.; Toko Shimura, B.Sc.; Minori Kawamoto, M.Sc.; Minako Sugishima, B.Sc.; Yasuyuki Mio, M.D., Ph.D. (F&S Reports, 2024)
Objective: To investigate whether artificial removal of zona pellucida (ZP) at the pronuclear stage improves good-quality embryos and blastocyst development in patients with difficulty conceiving because of severe fragmentation in early-cleavage stage. Design: Exploratory investigation. Setting: Reproductive center. Patient(s): Thirty-four patients scheduled for assisted reproductive technology (ART) treatment in our clinic between February 2020 and January 2021 were selected to undergo ZP removal according to their ART-related medical history. In total, 173 two pronuclei zygotes were obtained, with 101 allocated to the ZP-free group and 72 to the ZP-intact group. All patients had zygotes allocated in both ZP-free and ZP-intact groups. Intervention(s): Oocytes that were confirmed to be normally fertilized were placed in sucrose-containing HEPES medium for approximately 5 minutes and cultured under one of the following two conditions: ZP-free, in which the ZP was completely removed from the ooplasm by laser irradiation and a medium-blowing method with a biopsy pipette; and ZP-intact. Subsequently, embryos were either freshly transferred on day 2 (ZP-intact group only, according to patients’ wishes), or day 5/6, or they were cryopreserved on day 5/6/7 for future embryo transfer cycles for both groups. Main Outcome Measure(s): Rates of good-quality embryos, blastocyst development, morphologically good-quality blastocyst development, and cryopreservation. Result(s): In ZP-free embryos, the inter-blastomere adhesion was not disturbed and the fragmentation was significantly decreased that resulted into significant improvement in all measured parameters compared with the ZP-intact group. Conclusion(s): Artificial ZP removal at the pronuclear stage may prevent excessive fragmentation leading to good-quality blastocysts. Moreover, patients with recurrent ART failure may achieve successful pregnancies.